Ships going slow in reducing their NOx emissions: changes in 2005–2012 ship exhaust inferred from satellite measurements over Europe. (9th July 2015) - Boersma, K Folkert; Vinken, Geert C M; Tournadre, Jean
Abstract: We address the lack of temporal information on ship emissions, and report on rapid short-term variations of satellite-derived ship NOx emissions between 2005 and 2012 over European seas. Our inversion is based on OMI observed tropospheric NO2 columns and GEOS-Chem simulations. Average European ship NOx emissions increased by ∼15% from 2005 to 2008. This increase was followed by a reduction of ∼12% in 2009, a direct result of the global economic downturn in 2008–2009, and steady emissions from 2009 to 2012. Observations of ship passages through the Suez Canal and satellite altimeter derived ship densities suggests that ships in the Mediterranean Sea have reduced their speed by more than 30% since 2008. This reduction in ship speed is accompanied by a persistent 45% reduction of average, per ship NOx emission factors. Our results indicate that the practice of 'slow steaming', i.e. the lowering of vessel speed to reduce fuel consumption, has indeed been implemented since 2008, and can be detected from space. In spite of the implementation of slow steaming, one in seven of all NOx molecules emitted in Europe in 2012 originated from the shipping sector, up from one in nine in 2005. The growing share of the shipping contributions to the overall European NOx emissions suggests a need for the shipping sector to implement additional measures to reduce pollutant emissions at rates that are achieved by the road transport and energy producing sectors in Europe.